The Effect of Android-based DM Diet Education Program on Eating Behavior and Blood Glucose Level of DM Type 2 Patients in Health Centers in Bandung City - Taufik, Ides Haeruman; Kustiyah, Lilik; Dwiriani, Cesilia Meti (Universitas Pendidikan Indonesia, 2019)
The purpose of this study was to examine the effect of Android-based DM diet education program on changes in eating behavior and blood glucose levels. The study design used in this study was a cluster randomized control trial with a pre-post intervention. The study involved 33 DM patients in the intervention group and 37 patients in the DM control group. The proportion of female subjects was higher than male subjects in the treatment group. Nutrition education intervention, with application media, significantly increased DM disease severity perception score (p = 0.000), expectations of DM treatment (p = 0.000), eating habits practice (p = 0.025), and fasting blood sugar examination (p = 0.414). However, compared to counseling, the increase in perception of the severity of DM disease was significantly different, but for DM treatment expectation perceptions, the practice of eating habits, and fasting blood sugars were not significantly different. Despite increased disease severity perception scores, DM treatment expectations, practice of eating habits, and fasting blood sugar checks in the application group were higher than in the extension group. Thus, the use of both nutritional education intervention methods has a positive impact on increasing perceptions of severity, treatment expectations, practice of eating habits, and fasting blood sugar of DM type 2 patients.